Cultural Marginalization of Bride Price (Uang Panai) in Bugis-Makassar Society, Indonesia: A Case Study of MUI Fatwa - Sanusi, Nur Taufiq; Amin, Muhammadiyah; Muhammad Alwi HS,; Parnnsih, Iin (Journal of Al-Tamaddun, 2025)
This article seeks to elucidate the marginalization of uang panai within the Bugis-Makassar culture, as addressed in the islamic ruling (fatwa) issued by the MUI of South Sulawesi. Furthermore, it aims to provide a critical examination and potential solutions to enhance the significance of uang panai in contemporary Bugis-Makassar society. The central thesis posits that local culture functions as a socially constructed choice, with its continuity reflecting tangible benefits for its adherents. This study employs a literature review methodology, utilizing the MUI fatwa of South Sulawesi Province, Number: 02 of 2022, concerning Uang panai as the primary source for analysis. It is further explored through a sociocultural lens and informed by critical discourse analysis. The findings indicate that the MUI's fatwa has shifted the nature of uang panai from being obligatory (binding) within Bugis culture to merely permissible (non-binding). The status of uang panai, which is culturally akin to bride price, is positioned by the MUI as subordinate to bride price, reducing it to a mere complement. These varied perspectives held by the MUI exemplify the marginalization of uang panai, a cultural element that warrants preservation. Therefore, it is imperative to foster collaboration among diverse stakeholders to uphold the essence, value, and significance of uang panai. As a recognized authority in Islamic jurisprudence, the MUI must play a leading role in establishing partnerships with relevant parties, particularly traditional leaders and the Bugis-Makassar community, given that the issue of uang panai is fundamentally cultural rather than religious, having existed since the pre-Islamic era.